REPRESENTASI KONFLIK POLITIK DALAM NOVEL LENTERA BATUKARU KARYA PUTU SETIA - Luh Putu Ema Noviyanti; Ribut Wahyu Eriyanti; Inka Krisma Melati (Universitas Muhammadiyah Kotabumi, 2022)
Literature and politics come from the results of interactions between humans with one another. Politics and humans have a relationship with each other. The aims of this study are (1) representation of political conflict (2) the causes of political conflict and (3) the impact of political conflict in the novel. The object used is the novel Lantern Batukaru by Putu Setia. The method used in this research is descriptive qualitative method, explaining the facts that occur in the novel. The data collection technique is a note-taking technique by reading the entire contents of the novel, then taking notes on important things that can support the research. Data analysis is done by interpreting the data in accordance with the theory. The results of this study indicate that (1) there was a political conflict that occurred during the New Order era which was dominated by party power and suppression due to ideological differences between parties (2) the factors causing political conflict were the dissemination of information that was not known to be true so that it harmed and caused victims. soul (3) the impact of political conflict in the presence of murder, crackdown and sexual harassment committed on minors.